Reconstruction of the worldview as strategy for environmental survival and sustainability - Ahmed Shogar, Ibrahim Adam (Springer Berlin Heidelberg, 2011)
The current ecological crisis is a matter of urgent global concern that seeks global solutions and sincere cooperation of nations and all parties of the human community: experts, policymakers, organizations and publics. The relevant solution, however, sought to be found associated with a precise identification and clear vision of root causes which, consequently, guide to the development of valid theories that capable to address the issue from its various dimensions. Although the distinguished scholars of various disciplines across the glob have been suggesting solutions of different kinds to the problem, they agree that the major part of environmental crisis comes from human actions. However, more significantly, scholars are in agreement that human actions are determined by his ideas and beliefs. This factor obviously identifies the strategic approach to deal with our ecological crisis; that is to rebuild our ideas and beliefs towards nature, i.e. reconstruction of the worldview. This work examines this hypothesis which asserts that the environmental crisis which experienced by mankind today are mainly due to his world view; i.e. misconception of the true relationship between man, nature and the ultimate truth. The study focuses on philosophical foundations of man- nature relationship, with objective of providing useful insights and perspectives that might contribute to uncover the root causes of our environmental crisis; and to establish a new united vision that capable to maintain the indispensable friendship of man and nature. To achieve these goals the study shall focus on the view that both man and nature are creatures of one Creator. However, nature has been made to serve man, not as a machine dominated by human, but as “Amanah” or “Trust” which capable for utilization not destruction. Nature, according to this concept, has two main functions: to serve man in his physical needs, and to guide him morally to the right path, i.e. towards discovery of the Creator and His great wisdom in the natural phenomena.